Abdomino-perineal Resection of the Rectum in a Haemophilic - Christie, T. H; Graham-Stewart, C. W; Ingram, G. I. C (Thrombosis and Haemostasis, 1960)
A moderately affected haemophilic aged 69 years, with about 10% of the normal plasma level of AHG, underwent abdomino-perineal resection of the rectum for carcinoma, under cover of bovine and porcine AHG.The post-operative course was complicated by the necessity of plugging the perineal wound to arrest operative haemorrhage from a vessel in the prostatic capsule; and considerable bleeding occurred on two occasions when the packs were removed. Otherwise, there was no abnormal bleeding.The management of the case is described, and technical details are discussed from the points of view of the surgeon, the anaesthetist and the haematologist.The Biggs’ AHG assay procedure was slightly modified to save time and stock haemophilic plasma. The importance of frequent assays is stressed.The anaesthetist remained responsible for the intravenous drips throughout the post-operative course.